Effects of High Fluoride and Low Iodine on Thyroid Function in Offspring Rats - Ya-ming GE; Hong-mei NING; Xin-li GU; Mei YIN; Xue-feng YANG; Yong-hua QI; Jun-dong WANG (Journal of Integrative Agriculture, 2013)
Thirty-two Wistar rats were divided randomly into four groups of eight with six females and two males in each group. The rats were exposed to high fluoride drinking water (45 mg F− L−1 from 100 mg NaF L−1), low dietary iodine (0.0855 mg kg−1), or both together in order to assess the effects of these three regimens on the thyroid function of the offspring rats. After the animal model was established, the offspring rats were bred and 10-, 20-, 30-, 60-, and 90-d-old rats were used for the experiment. The treatments for the offspring rats were the same as those of their parents. In comparison with control rats, the relative thyroid glands were changed by three regimens, but the mean values of thyroid weight in the experimental groups saw no marked difference. Serum TT3 levels were increased in all stages in the low iodine (LI) group. In the high fluoride (HiF) group, increase in TT3 levels was observed except in 20-d-old rats. Decrease in TT3 at 20- and 90-d and increase in TT3 at 30- and 60-d were found in HiF+LI group. Serum TT4 levels first saw an increase, and then dropped in the LI and HiF+LI group. However, an increase in TT4 was found in the HiF group. The levels of TSH in serum rocketed at d 20, and then dropped in the next stages in experimental groups. The results suggested that thyroid disorder could be induced by high flroride in drinking water, low iodine diet, or both of them. Exposure time to fluoride or low iodine diet was one of the important factors that fluoride can induce the development of thyroid dyfunction.